From Policies to Practice: Governance Gaps in Climate and Disaster Reduction in Nepal’s Riverine Communities - Sigdel, Goma; Pandey, Chandra Lal; Shrestha, Reshma; Niraula, Prakriti; Kafle, Karuna (NPRC Journal of Multidisciplinary Research, 2026)
Background: Riverine communities in Nepal face escalating climate-induced disasters, yet governance gaps between national policies and local implementation remain poorly understood. This study examines how climate change and disaster risk reduction policies are translated into practice in the Kamala River Basin.Objectives: We investigate (1) how riverine communities perceive and operationalize climate and DRR policies, and (2) the key disconnects between policy assumptions and local realities and what governance reforms are needed to bridge this gap.  Methods: Employing a mixed-methods approach in two municipalities (Siraha and Dudhauli) of the Kamala River Basin (2024-2025), we collected household surveys (n=408), key informant interviews (n=21), focus group discussions (n=2), and conducted policy document analysis to explore social, economic, institutional, environmental, and infrastructural dynamics.Findings: Policy awareness among communities is critically low: >70% of respondents are unaware of formal disaster response procedures, and